Comparison of vascular risk profile and clinical outcomes among patients with central (branch) retinal artery occlusion versus amaurosis fugax - Diel, Norma J.; Gerner, Stefan T.; Doeppner, Thorsten R.; Juenemann, Martin; Maxhuni, Toska; Frühwald, Tobias; Worm, Andre; Alhaj Omar, Omar; Lytvynchuk, Lyubomyr; Struffert, Tobias; Bauer, Pascal; Huttner, Hagen B.; et al. (My University, 2024)
Background: Retinal artery occlusions lead to sudden, painless vision loss, affecting millions globally. Despite their significance, treatment strategies remain unestablished, contrasting with acute ischemic stroke (AIS), where IVT has proven efficacy. Similar to AIS, retinal artery occlusions demand urgent evaluation and treatment, reflecting the principle "time is retina". Even for patients with transient monocular vision loss, also known as amaurosis fugax (AF), pertinent guidelines meanwhile recommend immediate emergency assessment in a specialized facility. However, data on the clinical benefit and comparability with persistent occlusions are missing. This study aimed to compare the results of a comprehensive stroke-workup among patients with persistent retinal artery occlusions (RAO), including both central retinal (CRAO) and branch retinal artery occlusion (BRAO) and those with AF. Methods: Conducted at the University Hospital Giessen, Germany, this exploratory cross-sectional study enrolled patients with transient or permanent unilateral vision loss of non-arteritic origin. The primary outcome were differences between the two groups RAO and AF with regard to cardiovascular risk profiles and comorbidities, vascular and pharmacological interventions and clinical neurological and ophthalmological outcomes. Secondary outcome was a sub-group analysis of patients receiving IVT. Results: Out of 166 patients assessed, 76 with RAO and 40 with AF met the inclusion criteria. Both groups exhibited comparable age, gender distribution, and cardiovascular risk profiles. Notably, RAO patients did not show significantly more severe vascular comorbidities than AF patients. However, AF patients received vascular interventions more frequently. Pharmacological intervention rates were similar across groups. RAO patients had slightly worse neurological outcomes, and IVT did not yield favorable ophthalmological outcomes within any observed patients. Conclusion: The study found similar vascular burden and risk factors in patients with RAO and AF, with implications for clinical workflows. IVT for RAO may only be effective in very early treatment windows. This emphasizes the need for public awareness and collaborative protocols between ophthalmologists and neurologists to improve outcomes.
Keywords: ddc:610